Geographical Proximity is not Enough: How Culture Shaped Placement, Spatiality, and the Outcomes of the Arab Spring’s Uprising (Glocalism: Journal of Culture, Politics and Innovation, 2017)
This paper investigates the phenomenon of the Arab Spring against the background of cultural traditions and attitudes that sustained these protests and carried them across borders of more than twenty countries in the Middle East in a move of cultural contagion of conflict (Gelfand et al. 2012). Tracing the placement and spatiality of the Arab Spring uprisings, their media and ideascapes (Appadurai 1990), this paper draws upon theoretical frameworks of Homi Bhabha’s (2004) third space, Margaret Kuhn’s (2003) radical space, and Geert Hofstede’s (2014) cultural indicators. Given the information about self-immolations as the events that stirred the uprisings in the Arab Spring’s countries in 2010-2012, it explores how patterns of contagion of conflict have been operating through specific cultural conditions during successful protests that led to the change of regime as opposed to failed protests that did not. The paper offers a cultural profile of the Arab Spring countries, discussing its implications for the countries’ governance regarding the existence of inter-networked places of protests, significance of their cultural traditions, and their linkage to success or failure of the protests.
Keywords: place; third space; radical space; the Arab Spring; cultural dimensions